2014
DOI: 10.1111/jofi.12130
|View full text |Cite
|
Sign up to set email alerts
|

The Real Effects of Government‐Owned Banks: Evidence from an Emerging Market

Abstract: Using plant‐level data for Brazilian manufacturing firms, this paper provides evidence that government control over banks leads to significant political influence over the real decisions of firms. I find that firms eligible for government bank lending expand employment in politically attractive regions near elections. These expansions are associated with additional (favorable) borrowing from government banks. Further, these persistent expansions take place just before competitive elections, and are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
1
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(113 citation statements)
references
References 52 publications
6
91
1
15
Order By: Relevance
“…At least part of the government-driven credit expansion took the form of direct loans from BNDES. According to Carvalho (2014), those were given in exchange to employment expansion in places with tight electoral campaigns. However, this cannot be the whole story, since earmarked loans given through private banks and nonearmarked government-owned banks have also expanded substantially.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At least part of the government-driven credit expansion took the form of direct loans from BNDES. According to Carvalho (2014), those were given in exchange to employment expansion in places with tight electoral campaigns. However, this cannot be the whole story, since earmarked loans given through private banks and nonearmarked government-owned banks have also expanded substantially.…”
Section: Discussionmentioning
confidence: 99%
“…The political view of government intervention in the banking sector is supported by Sapienza (2004) and Carvalho (2014). The former, in a study of Italian banks and firms, found 6 that the lending behavior of government-owned banks is affected by the electoral results of the party affiliated with the bank.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These banks mainly lend to large international firms, the public sector, and the government. The main finding in these studies is that the large, central government-owned banks exhibit underperformance and inefficient credit allocation because of agency problems, political influence, fraud and corruption (e.g., La Porta et al, 2002;Sapienza, 2004;Dinç, 2005;Illueca et al, 2014;Carvalho, 2014). We note that virtually all studies in this field are based on data from relatively large, central or regional government-owned banks.…”
mentioning
confidence: 99%
“…Political influence on lending behavior of public banks has been widely documented in the literature (e.g., La Porta et al, 2002;Sapienza, 2004;Dinç, 2005;Carvalho, 2014). As described earlier, most of these studies focus on large public banks that are owned or controlled by central governments, hence, their settings are not closely comparable to ours.…”
Section: Modelmentioning
confidence: 73%